The Effectiveness of the Reading, Mindmapping, and Sharing (RMS) Learning Model in Improving Students' Learning Outcomes in Road and Bridge Construction - Siti Aminah; Dady Suryadi; Sri Rahayu (Universitas Negeri Yogyakarta, 2023)
Background: The principal aim of this study was to evaluate the impact of employing the Reading, Mind Mapping, and Sharing (RMS) learning strategy on student learning outcomes within a course focused on road and bridge construction. The motivation for c conducting this research arose from the observation that SMK Negeri 1 Sumedang students exhibited inferior performance compared to their KKM peers in the context of road and bridge construction.Methods: Furthermore, limited research has explored the implementation of student-centred educational models within this specific realm. To address these concerns comprehensively, researchers opted to utilize a quasi-experimental strategy encompassing a non-equivalent control design. Data collection involved gathering information before the implementation of intervention methods through pre-tests and subsequently following up with post-tests post-intervention.Result: A detailed analysis of the gathered data demonstrated clear discrepancies in learning outcomes between both experimental and control groups. Additionally, A notable discovery involved calculating normalized gain (N Gain) values for participants utilizing RMS model techniques. Such calculations indicated a moderate level of enhancement, as apparent through median value determinations yielding 0.553. Additionally, outcomes among exceptionally effective participants yielded impressive N gain percentages, standing at around 55.26 percent.Conclusion: Accordingly, it can be concluded without doubt that implementing teaching techniques based on RMS (Reading, Mind Mapping, and Sharing) principles hold substantial promise in enhancing student comprehension levels within road and bridge construction curriculums.